2006
DOI: 10.1152/ajplung.00391.2004
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response of tracheobronchial epithelial cells to endotoxin

Abstract: Respiratory epithelial cells play a crucial role in the inflammatory response in endotoxin-induced lung injury, an experimental model for acute lung injury. To determine the role of epithelial cells in the upper respiratory compartment in the inflammatory response to endotoxin, we exposed tracheobronchial epithelial cells (TBEC) to lipopolysaccharide (LPS). Expression of inflammatory mediators was analyzed, and the biological implications were assessed using chemotaxis and adherence assays. Epithelial cell nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
5
21
0
4
Order By: Relevance
“…In addition, other pulmonary cells may contribute to the secretion of these cytokines in BALF. Several studies have suggested pulmonary epithelial cells as potential sources of TNF-a production, a theory that is supported by the fact that TNF-a protein has been localised to alveolar epithelial cells by immunohistochemical staining [30][31][32]. In contrast, according to the present data, the levels of IL-10 mRNA and protein in the BALF of sarcoidosis patients correlated well, indicating that BALF IL-10 was primarily produced by BALF cells in sarcoidosis.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, other pulmonary cells may contribute to the secretion of these cytokines in BALF. Several studies have suggested pulmonary epithelial cells as potential sources of TNF-a production, a theory that is supported by the fact that TNF-a protein has been localised to alveolar epithelial cells by immunohistochemical staining [30][31][32]. In contrast, according to the present data, the levels of IL-10 mRNA and protein in the BALF of sarcoidosis patients correlated well, indicating that BALF IL-10 was primarily produced by BALF cells in sarcoidosis.…”
Section: Discussionsupporting
confidence: 76%
“…This statement can also be applied to tracheobronchial epithelial cells. In a previous work from our group, we were able to demonstrate that the intrinsic apoptosis pathway is activated at 24 h of LPS stimulation [10]. Results of the current study show that the process of apoptosis is already initiated at earlier time-points upon stimulation with LPS.…”
Section: Discussionsupporting
confidence: 66%
“…At 4 h of injury, apoptosis rate decreased by 19% (range 35%) under hypoxia and by 32% (range 39%) with LPS, respectively (P < 0·05). In tracheobronchial epithelial cells, apoptosis increased upon 24 h of LPS stimulation, as shown previously with the help of a terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick-end labelling (TUNEL) staining [10].…”
Section: Hypoxia-and Endotoxin-induced Apoptosis In Target Cellssupporting
confidence: 74%
“…Apoptosis in cultured A549 cells [37] and tracheobronchial epithelial cells [38] treated with LPS has been reported only with very high doses of LPS (100 mg?mL -1 ), which are of questionable clinical significance. LPS-induced apoptosis in vivo probably is the result of more complex convergence of death signals, including the Fas/FasL pathway [8].…”
Section: Epo: Cytoprotective In Lung Epithelium R Macredmond Et Almentioning
confidence: 99%